Bit-Mouth Interaction in the Horse: A Multifactorial Analysis of Material, Geometry, Anatomy and Rider Influence - Rubin, Vendela (My University, 2026)
Understanding bit-mouth interaction in horses requires an integrated evaluation of material properties, bit geometry, equine oral anatomy and rider-related factors. This study employed a triangulated qualitative design combining a structured literature review, mechanical material analysis and expert interviews to investigate how these factors influence pressure distribution and the risk of bit-related injuries. Mechanical data demonstrated substantial differences between commonly used bit materials, where metals provided greater structural stability but increased the risk of tooth-related injuries, while softer materials such as TPU and leather reduced stress concentrations on the teeth yet were associated with a higher prevalence of lesions induced from friction. Bit geometry and fitting emerged as equally critical determinants, with thin, correctly sized mouthpieces offering superior stability and reduced tissue compression. Expert interviews highlighted underdocumented clinical findings, including low grade mobility and excessive wear of the P2 teeth, as well as the central role of rider balance, rein tension and technique in modulating mechanical load. Variation in equipment use was identified as an important, but under-recognized strategy for reducing cumulative stress on the tissue. Overall, the findings demonstrate that bit–mouth interaction is multifactorial and cannot be understood through material or design parameters alone. An integrated approach that considers mechanical behavior, anatomical prerequisites and rider influence is essential for improving bit selection, fitting practices and equine welfare.
Keywords: bit-related injuries, equine oral cavity, bit wear, biomechanics horse bits, horse bits, equine oral injuries.